Multiple factors based adaptive laboratory evolution strategy enhances DHA production in Aurantiochytrium sp. PKU#Mn16 by rewiring key metabolic pathways - Xueyan Ding; Xingyu Zhu; Yuetong Zhao; Ningdong Xie; Guangyi Wang (Microbial Cell Factories)
Abstract Background Marine protists Aurantiochytrium are recognized as promising sources for commercial lipid production, particularly due to their ability to produce high-value natural compounds like docosahexaenoic acid (DHA). However, wild-type strains isolated from natural environments typically fail to meet commercial demands for DHA yields, partly because they are poorly adapted to the decreased pH conditions encountered during fermentation. Results In this study, we employed a staged acidic adaptive laboratory evolution (ALE) strategy to develop a high DHA-producing strain from Aurantiochytrium sp. PKU#Mn16. By optimizing oxygen and temperature levels under low pH conditions, ALE resulted in a 171.4% increase in DHA concentration in the ALE strain compared to the wild-type strain. Comparative transcriptomics revealed that ALE enhanced the expression of key enzymes in glycolysis and the polyketide synthase (PKS) pathway during both early (metabolic peak) and late (metabolic decline) fermentation stages, promoting growth and polyunsaturated fatty acid synthesis. Additionally, key enzymes in the tricarboxylic acid (TCA) cycle and pentose phosphate (PPP) pathway were upregulated at early and late stages, respectively, suggesting differential ATP/NADPH supply mechanisms that drive DHA accumulation. Notably, the upregulation of glycerol kinase (GK) indicates the potential for using glycerol as an alternative carbon source to further enhance DHA production in our ALE strain. Conclusions In this study, Aurantiochytrium sp. PKU#Mn16 was successfully acclimated using a synergistic approach combining high dissolved oxygen, low temperature, and citric acid-induced acidity. This strategy yielded significant increases of 106.3% in biomass, 243.8% in total fatty acid yield, and 171.4% in DHA yield. Transcriptomic analysis revealed extensive rewiring of central carbon and lipid metabolism, including the upregulation of PKS pathway enzymes and enhanced supply of ATP, NADPH, and acetyl-CoA. Additionally, reduced competing secondary metabolic fluxes optimized substrate allocation. This innovative acclimation strategy not only sheds light on the molecular mechanisms driving efficient fatty acid and DHA production but also lays the groundwork for future comparative genomics and genetic editing efforts aimed at further boosting yields of fatty acids and other natural secondary metabolites in thraustochytrids.